2014
DOI: 10.1111/ced.12402
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasiform exfoliative erythroderma induced by golimumab

Abstract: Golimumab is a fully human anti-tumour necrosis factor (TNF)-α monoclonal antibody approved for use in the treatment of active rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis. Psoriasis induced by treatment with anti-TNF drugs is well documented, but to our knowledge, the development of clinical features of psoriasiform exfoliative erythroderma during treatment with golimumab has not been previously described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…9 Of note, treatment with certolizumab pegol and golimumab has also been associated with anti-TNF-induced psoriasis in RA. 19,20…”
Section: Tumor Necrosis Factor Inhibitor-induced Psoriasis In Inflammmentioning
confidence: 99%
“…9 Of note, treatment with certolizumab pegol and golimumab has also been associated with anti-TNF-induced psoriasis in RA. 19,20…”
Section: Tumor Necrosis Factor Inhibitor-induced Psoriasis In Inflammmentioning
confidence: 99%
“…Two of the 17 patients in the GLM group developed psoriasis. Several studies have reported psoriasis caused by GLM, and care physicians should be aware of this adverse effect [ 31 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 Golimumab has also been implicated as a cause of PP in case reports of patients with rheumatoid arthritis but has not been linked to TNF antagonist-associated PP in IBD. 19 Furthermore, IBD patients were more likely to develop PP during TNF antagonist maintenance therapy. 15 Freling et al reported that 88.1% (52/59) patients were in clinical remission for their IBD when they developed psoriatic lesions.…”
Section: Ris K Fac Tor Smentioning
confidence: 99%
“…Conversely, Afzali and colleagues have suggested that patients who received adalimumab are more at risk of developing PP 13 . Golimumab has also been implicated as a cause of PP in case reports of patients with rheumatoid arthritis but has not been linked to TNF antagonist‐associated PP in IBD 19 …”
Section: Risk Factorsmentioning
confidence: 99%